Critical Thinking Ability and Self-Concept With Learning Outcomes of Class V Students' Citizenship Education School Base - Sabanah Putri Andini (International Journal of Students Education, 2024)
Studies literature this investigate connection between ability think critical, concept self, and results study Education Citizenship on student class V school base. With use method study systematic, research This obtain and evaluate information from various relevant sources, incl journal scientific, books text, and documents other. Analysis critical to sources information the disclose that ability think good criticism and draft positive self in a way significant contribute to results learn more tall in eye lesson Education Citizenship. Besides those, factors like motivation study and environment study also play role important in determine results study student. This findings own implications important for development education in level school basic, highlighting importance development ability think critical and draft positive self in increase quality education citizenship. Expected results this study can give valuable contribution for understanding and development education citizenship in level school base.